Surface hardness of hybrid ionomer cement after immersion in antiseptic solution - Anita Yuliati; Ajeng Kartika Sri Wardani (Dental Journal (Majalah Kedokteran Gigi), 2006)
Hybrid ionomer cement or resin modified glass ionomer cement is a developed form of conventional glass ionomer cement. This hybrid ionomer cement can be eroded if in direct contact with acid solution which will affect surface hardness. The aim of this study is to learn surface hardness of hybrid ionomer cement after immersion in methyl salicylate 0.06% (pH 3.6) and povidon iodine 1% (pH 2.9) solution. Sample of hybrid ionomer cement with 5 mm diameter and 3 mm thickness was immersed in sterile aquadest solution (control), methyl salicylate pH 3.6, povidon iodine pH 2.9 for 1 minute, 7 and 14 minutes. Surface hardness was measured with Micro Vickers Hardness Tester. The obtained data was analyzed statistically with ANOVA followed by LSD test. The result of hybrid ionomer cement after immersion in sterile aquadest, methyl salicylate 0.06% pH 3.6 and povidon iodine 1% pH 2.9 for one minute, showed no significant difference; while immersion for 7 and 14 minutes showed a significant difference. The conclusion states that hybrid ionomer cement after 14 minutes immersion in povidon iodine 1% pH 2.9 has the lowest surface hardness.